Endocrown as a restorative strategy in endodontically treated teeth: an integrative literature review - Robson de Lima GOMES; Andressa Cristina da Silva QUEIROZ; Viviane Maria Gonçalves de FIGUEIREDO (Faculdade São Leopoldo Mandic, 2022)
ABSTRACT With the consolidation of Adhesive Dentistry and the emergence of new aesthetic restorative materials, Endocrown has been studied as a rehabilitative option for endodontically treated teeth. This is an Integrative Literature Review, based on the PICO strategy, with articles selected from the databases of PubMed and BVS, with a period of time from 2011-2021. The database search strategy included the following keywords: ("Endocrown" OR "Endocrowns" OR "Endocrown Restoration" OR "no-post buildup" OR "adhesive endodontic crowns"). Inclusion criteria for this review were laboratory studies and observational clinical studies. Exclusion criteria were clinical case studies, literature review, systematic review and meta-analysis. Furthermore, articles that addressed only intraradicular retainers or other restorative strategies were also excluded. The selection of articles was based on abstracts. 5 articles were selected for analysis, obtaining data on the endocrown in relation to the stress on the tooth structure, aging, marginal adaptation, fracture resistance, endocrown versus conventional crown and integrity of the tooth structure. The findings in the literature are not yet established regarding the integrity of the dental structure, as the supporting evidence is limited. Only 1 in vitro article showed that dental failures in endocrowns are more favorable to repair and another 2 in silico studies show lower stress distribution on enamel, dentin and cement in the same restoration. Moreover, the restorative material seems to influence the possibility of fracture for both conventional crowns and endocrown restorations.